Media relations strategy of the public relations of the University of August 17, 1945 Surabaya in the maintenance of the image of the institution - Fadhilla, Adrian Ali; Rizqi, Muchamad; Pradana, Bagus Cahyo Shah Adhi (C-DISC, 2023)
This study aims to analyze the public relations media strategy in maintaining the image of the University of 17 August 1945 Surabaya. This type of research is descriptive qualitative research. The research subjects were Untag Surabaya public relations and mass media journalists. Data were collected using interview, observation and documentation methods. The collected data were then analyzed through data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, this research used triangulation technique. The results of this study indicate that the media relations strategy of Untag Surabaya Public Relations in maintaining the image of Universitas 17 August 1945 Surabaya is carried out in accordance with established procedures. This can be seen from the role of Untag Surabaya Public Relations in the form of publishing press releases, holding press conferences, placing advertorial advertisements to the appropriate segment of mass media through the media list. Public Relations of Untag Surabaya establishes a close relationship with mass media colleagues through media gathering events, provides media center facilities to work, gather information, establish two-way communication with journalists regarding the activities to be carried out.